Ungulate herbivores promote beta diversity and drive stochastic plant community assembly by selective defoliation and trampling: From a four‐year simulation experiment - Guo, Tongtian; Guo, Meiqi; Pang, Yue; Sun, Xiangyun; Ryo, Masahiro; Liu, Nan; Zhang, Yingjun (The Journal of ecology, 2024)
Ungulate herbivores shape grassland plant communities at multiple scales, ultimately affecting ecosystem function. However, ungulates have complex effects on grasslands, including defoliation, trampling, excreta return and their interactions. Moreover, the effects of ungulate density on grasslands are regulated by these three mechanisms. Nevertheless, how these three mechanisms affect biodiversity at multiple scales and community assembly remains poorly understood. Here, we conducted a 4‐year novel field experiment to disentangle the effects of defoliation, trampling, and excreta return by ungulates on plant community assembly in a temperate grassland in Inner Mongolia, China. This experiment set two different scenarios: moderate ungulate density (Moderate, characterised by selective defoliation and moderate trampling) and high ungulate density (Intense, characterised by non‐selective defoliation and heavy trampling), including different combinations of defoliation, trampling and excreta return in each scenario. We found that defoliation and trampling increased stochasticity in community assembly and promoted alpha and beta diversity under both scenarios. Specifically, defoliation promoted the coexistence of species with multiple resource acquisition strategies (higher functional trait diversity) by reducing interspecific competition; trampling tended to facilitate random species colonisation. Conversely, excreta return favoured grasses, promoting deterministic assembly and impacting species coexistence. Notably, selective defoliation in the Moderate scenario led to a dominance of stochastic processes during community assembly, whereas non‐selective defoliation still did not change the dominance of deterministic processes. Further, communities subject to selective defoliation were insensitive to changes in soil properties caused by trampling and excreta return, maintaining a high‐level beta diversity and the stochastic of community assembly. Synthesis: Our study provides important insights into the mechanisms by which ungulate herbivores influence plant community assembly, suggesting that defoliation and trampling have the potential to drive stochastic processes, while excreta return plays the opposite role. Our study also suggests that selective foraging by ungulates acts as stronger stochastic forces during community assembly compared to non‐selective defoliation. These results imply that considering ungulate feeding preferences and foraging behaviour in grassland management will help prevent biodiversity loss and biotic homogenisation. 摘要 有蹄类食草动物在多个尺度上塑造草地植物群落，最终影响生态系统功能。然而，有蹄类动物对草原的影响是复杂的，包括采食、践踏和排泄物返还。此外，有蹄类动物密度对草地的影响也通过这三种机制来调控。然而，人们对这三种机制如何影响植物多样性和群落构建的认识仍然不足。 我们在中国内蒙古的温带草原上进行了一项为期4年的野外实验，以厘清有蹄类动物的采食、践踏和排泄物返还对植物群落构建的影响。该实验设定了两种不同的情景:中等有蹄类动物密度(Moderate，以选择性采食和适度践踏为特征)和高有蹄类动物密度(Intense，以非选择性采食和重度践踏为特征)。每种情景中包括采食、践踏和排泄物返还的不同组合。 我们发现，采食和践踏增加群落构建的随机性，促进了两种情景下的α和β多样性。具体来说，采食通过减少种间竞争，促进具有多种资源获取策略的物种共存(更高的功能多样性)；践踏则倾向于促进物种的随机定殖。相反，排泄物返还有利于禾本科植物生长，促进确定性过程，进而影响多物种共存。值得注意的是，在Moderate情景下的选择性采食导致群落构建中随机过程占主导地位，而非选择性采食并没有改变确定性过程的主导地位。此外，经过选择性采食处理的群落对践踏和排泄物返还引起的土壤性质变化不敏感，保持了较高的β多样性和随机的群落构建模式。 我们的研究为理解有蹄类食草动物影响植物群落构建的机制提供重要见解，表明采食和践踏驱动了随机过程，而排泄物返还则起相反作用。我们的研究还发现与非选择性采食相比，有蹄类动物的选择性采食在植物群落构建过程中起到了更强的随机效应。综上，在草地管理中考虑有蹄类动物的采食偏好和食草行为将有助于防止草地生物多样性丧失和同质化。 This study provides insights into the mechanisms by which ungulate herbivores influence plant community assembly, suggesting that defoliation and trampling drive stochastic processes, while excreta return plays the opposite role. Selective foraging under moderate ungulate density acts as stronger stochastic forces compared to non‐selective defoliation and leads to a less sensitive community response to trampling and excreta return.